Efektivitas Penggunaan Herbarium Book Sebagai Media Pembelajaran Morfologi Tumbuhan Terhadap Hasil Belajar Mahasiswa Program Studi Pendidikan BiologiUniversitas Pasir Pengaraian - Dahlia (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2024)
Learning media has an important role in supporting the learning process. An educator must be able to create an effective and fun learning atmosphere. The use of visual media in the form of a herbarium book is one way that can be done. The herbarium book learning media is able to help students understand the material presented, so that learning objectives can be achieved. This study aims to determine the effectiveness of the use of herbarium book as a learning medium on leaf shape material on student learning outcomes in the 3rd semester of Biology at Pasir Pengaraian University. This type of research is a quasi experiment. The design used is a one-group pretest-posttest design. The population in this study were all students of the Biology Education Study Program, FKIP UPP. The research sample was the 3rd semester students of Biology Education FKIP UPP determined by purposive sampling technique. The data analysis technique used validity test, normality test, homogeneity test, and Wilcoxon mean difference using SPSS 16 software. Wilcoxon test obtained sig value. (2-tailed) of 0.000. Because the value of 0.000 is smaller than 0.05 with a mean pretest value of 26.04 and a mean posttest of 68.79, H0 is rejected and Ha is accepted. This means that the herbarium book media is effectively used to improve student learning outcomes of the biology education study program, Faculty of Teacher Training and Education, University of Pasir Pengaraian.